ßS-Haplotypes in sickle cell anemia patients from Salvador, Bahia, Northeastern Brazil - Gonçalves,M.S. (2003)
ßS-Globin haplotypes were studied in 80 (160 ßS chromosomes) sickle cell disease patients from Salvador, Brazil, a city with a large population of African origin resulting from the slave trade from Western Africa, mainly from the Bay of Benin. Hematological and hemoglobin analyses were carried out by standard methods. The ßS-haplotypes were determined by PCR and dot-blot techniques. A total of 77 (48.1%) chromosomes were characterized as Central African Republic (CAR) haplotype, 73 (45.6%) as Benin (BEN), 1 (0.63%) as Senegal (SEN), and 9 (5.63%) as atypical (Atp). Genotype was CAR/CAR in 17 (21.3%) patients, BEN/BEN in 17 (21.3%), CAR/BEN in 37 (46.3%), BEN/SEN in 1 (1.25%), BEN/Atp in 1 (1.25%), CAR/Atp in 6 (7.5%), and Atp/Atp in 1 (1.25%). Hemoglobin concentrations and hematocrit values did not differ among genotype groups but were significantly higher in 25 patients presenting percent fetal hemoglobin (%HbF) > or = 10% (P = 0.002 and 0.003, respectively). The median HbF concentration was 7.54 ± 4.342% for the CAR/CAR genotype, 9.88 ± 3.558% for the BEN/BEN genotype, 8.146 ± 4.631% for the CAR/BEN genotype, and 4.180 ± 2.250% for the CAR/Atp genotype (P = 0.02), although 1 CAR/CAR individual presented an HbF concentration as high as 15%. In view of the ethnic and geographical origin of this population, we did not expect a Hardy-Weinberg equilibrium for CAR/CAR and BEN/BEN homozygous haplotypes and a high proportion of heterozygous CAR/BEN haplotypes since the State of Bahia historically received more slaves from Western Africa than from Central Africa.